Postoperative antibiotic use in patients with unilateral purulent chronic rhinosinusitis. Issue 4 (22nd July 2021) - Gordon, Alex; Benedict, Peter; Marcus, Sonya; Kingery, Matthew; Lebowitz, Richard A.; Lieberman, Seth M.
Abstract: Objectives: To describe our experience with the use of postoperative antibiotics in the management of unilateral chronic rhinosinusitis (CRS) patients with active infection at the time of surgery, and to evaluate the need for routine postoperative antibiotic administration in this population. Methods: This retrospective chart review analyzed the medical records of all patients who underwent endoscopic sinus surgery for unilateral purulent CRS between November 2013 and September 2019 at a tertiary care center and who were not prescribed routine postoperative antibiotics. Duration of time until normalization of sinus cavities and whether antibiotics were ultimately prescribed for persistent infectious signs and symptoms were recorded. Patient characteristics and findings were analyzed to determine if any of the evaluated parameters were associated with the need for postoperative antibiotics. Results: Sixty‐nine patients were included in the study. Thirty‐three (47.8%) did not require antibiotics during the postoperative period. The average time to sinus normalization was 8.1 weeks (range 1‐24 weeks) for patients who received antibiotics and 5.7 weeks (range 1‐16 weeks) for those who did not receive antibiotics ( P  = .066). No evaluated variables were associated with antibiotic use on univariate or multivariate analysis. Conclusion: Postoperative antibiotics were not necessary to normalize infected sinus cavities for nearly half of patients with unilateral purulent CRS in this series. Further studies are needed to better delineate which patients would derive benefit from postoperative antibiotics. Level of Evidence: Level IV.